PENGARUH GAYA KEPEMIMPINAN TERHADAP PRESTASI KERJA DI UNIVERSITAS KADIRI - Yap, Nonni; Rukmini, Meme; Pramana, Andy Chandra (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
Leadership style is one of the important things in advancing a company or organization. Leaders who have a vision and direction and have a good way of being towards employees will be an example for employees and will ultimately be able to improve employee performance. The purpose of this study is to find out the influence between leadership style and employee performance at Kadiri University. This type of research is quantitative research where the main data used in the form of figures are analyzed using statistics. The data collection technique used in this study is to use questionnaire techniques. The research variable consists of one independent variable that is leadership style and one dependent variable that is work performance. The collected data is then analyzed using a simple linear regression analysis. The results showed that there was a positive and significant influence between leadership styles on work performance. The results showed that the t count of leadership style variables was 8,817 greater than the t table of 2,039 and the Sig value of 0.000 was smaller than 0.05. The R2 determination coefficient obtained a yield of 0.715 or 71.5% which means that the leadership style is able to affect work performance by 71.5% while the rest is influenced by other variables